The Effect of Electronic Payment Instruments on the Lifestyle of the Millennials in the Jabodetabek - Rindah Febriana Suryawati; Septina Puspitasari; Izmi Dwira Eriani (TIJAB (The International Journal of Applied Business), 2023)
Background: Electronic payment instrument provides easier medium of daily transaction among millennial. The ease of use of electronic payment leads to a need to investigate whether it has an impact on millennial generation lifestyle. Objective: This study aims to analyze the effect of using electronic payment instruments on millennial lifestyles. Method: Survey questionnaires were distribute in this study and resulted in 191 questionnaires to be analyzed using Structural Equation Modelling. Results: The results showed that there are positive and significant effect of convenience on activities, interests, and opinions, usefulness on activities and ideas, and the development of usage attitudes on claims and statements. Meanwhile, efficacy's effect on interest and usage attitude's impact on activities has a positive but not significant effect. Conclusion: Three manifest variables: perceived ease of use, perceived usefulness, and attitude toward using, are factors that affect the use of electronic payment instruments. The electronic payment use was also proves as millennial lifestyle. Further, factors affecting millennial activity of using such payment method are: perceived ease of use and perceived usefulness. While factors affecting millennial interest to use such payment method are attention toward using and perceived ease of use. Factors affecting millennial opinion of using such payment method are perceived ease of use, attention toward using, and perceived ease of use. This research implies that the development of electronic payment instruments should consider and improve the security, backup systems and database recovery to support the activity and interest of using electronic payment instruments. Keywords: electronic payment; lifestyle; millennial; sem; technology acceptance model